Public deliberation to assess patient views on biosimilar medication switching for the treatment of inflammatory bowel disease - Kerry A. Ryan; Shirley Cohen-Mekelburg; Jessica A. Baker; Eileen M. Weinheimer-Haus; Chris Krenz; Jason K. Hou; Raymond De Vries; Akbar K. Waljee (BMC, 2024)
Abstract Background Biosimilars are highly similar, but not identical, versions of originator biologic medications. Switching patients to biosimilars presents an opportunity to mitigate rising drug costs and expand patient access to important biologic therapies. However, decreased patient acceptance and adherence to biosimilar medications have been reported, which can lead to loss of treatment response, adverse reactions, and inefficient resource utilization. Understanding patient perceptions of biosimilars and biosimilar switching is needed to inform patient-centered care strategies that promote efficient resource utilization. Methods We used democratic deliberation methods to solicit the informed and considered opinions of patients regarding biosimilar switching. Patients with inflammatory bowel disease (IBD; n = 29) from the Veterans Health Administration (VHA) participated in 5-hour deliberation sessions over two days. Following educational presentations with experts, participants engaged in facilitated small group discussions. Transcripts and facilitators' notes were used to identify key themes. Participants completed surveys pre- and post-deliberation to collect sociodemographic and clinical features as well as to assess IBD treatment knowledge and attitudes toward care and approaches to biosimilar switching. Results Five major themes emerged from the small group discussions in the context of biosimilar switching: 1) concerns about adverse consequences and unclear risk-benefit balance; (2) importance of communication and transparency; (3) desire for shared decision making and patient involvement in treatment decisions; (4) balancing cost-saving with competing priorities; and (5) advocating for individualized care and prioritization based on risk levels. These views led participants to favor approaches that prioritize switching the sickest patients last (i.e., those with poorly controlled disease) and that offer patients control and choices around biosimilar switching. Participants also expressed preferences for combining elements of different approaches to maximize fairness. Conclusions Approaches to biosimilar switching should consider patients' desires for transparency and effective communication about biosimilar switching and engagement in their medical decision-making as part of patient-centered care. Incorporating patient preferences around biosimilar switching is critical when navigating the quality and affordability of care in resource constrained settings, both within the VHA and in other healthcare systems.